A compound feed for increasing milk yield of a cow in lactation period
Patent Information
- Application Number
- CN202611263465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种提升泌乳期牛产奶量的配合饲料,解决了现有尿素类非蛋白氮饲料进入反刍动物瘤胃后往往水解速度过快,易引发动物的氨中毒风险
[0038] 1. This invention utilizes the cross-linking of borate ions from anhydrous sodium tetraborate with the hydroxyl groups of sodium lignosulfonate to form a three-dimensional cross-linked network framework within the compound feed, dispersing urea molecules within this network structure. This structural feature transforms urea release into a slow swelling and decomplexing process dependent on the polymer network, overcoming the defect of traditional surface-coated feeds where the coating breaks down after mechanical chewing by ruminants, leading to burst release. When the product exposes a new cross-section, the internal cross-linked network still provides steric hindrance, maintaining the stability of the feed's slow-release performance in the rumen.
Smart Images

Figure CN122911080A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of feed processing technology, specifically to a compound feed for increasing milk production in lactating cows. Background Technology
[0002] In ruminant farming, urea is often added to feed as a non-protein nitrogen source to supplement protein nutrition and reduce feeding costs. Lactating dairy cows have a high protein requirement, and the appropriate use of urea helps meet their nutritional needs and increase milk production. However, conventional urea, after entering the rumen of cattle, is rapidly hydrolyzed by urease secreted by rumen microorganisms, releasing a large amount of ammonia in a short period. When the rate of ammonia production exceeds the rate at which rumen microorganisms can synthesize and utilize microbial protein, excess ammonia is absorbed into the bloodstream, easily leading to ammonia poisoning in animals.
[0003] To slow down the release rate of urea, the industry typically uses physical surface coating technology to treat urea particles. This method controls the dissolution rate by forming a barrier layer on the urea surface. However, in actual feeding applications, the mechanical chewing behavior of ruminants often damages the coating layer on the particle surface. Once the coating is physically damaged, the internal urea is directly exposed to the rumen fluid, causing the original slow-release structure to fail and triggering a burst release of urea.
[0004] Besides surface coating, high-temperature melt blending to mix urea with other matrix materials is another common processing method. This process aims to disperse and encapsulate urea within the matrix to limit its hydrolysis. However, in actual processing, urea in a high-temperature molten state is highly susceptible to thermal deammoniation, which promotes intermolecular condensation to form biuret. Biuret is a substance with certain toxic side effects on ruminants; its increased content in feed directly affects product safety, thereby adversely impacting the animal's digestive system and production performance. Therefore, how to maintain the feed's slow-release properties against mechanical damage while effectively inhibiting thermal decomposition side reactions during processing to ensure product safety is a key technical problem that needs to be solved in the research and development of this type of non-protein nitrogen feed. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a compound feed that increases milk production in lactating cows. It solves the problem that existing urea-based non-protein nitrogen feeds often hydrolyze too quickly in the rumen of ruminants, easily leading to ammonia poisoning. Furthermore, the coating layer of conventional physically coated feeds is easily damaged during animal chewing, thus losing its slow-release effect. If urea is processed using a high-temperature melt blending process, it usually induces thermal decomposition side reactions and generates biuret byproducts, which to some extent limits the safe application of the product.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A compound feed for increasing milk production in lactating cows employs the following technical solution:
[0008] A compound feed for increasing milk production in lactating cows is made from the following raw materials in parts by weight: 75-80 parts urea, 10-15 parts sodium lignosulfonate, 6-8 parts zinc sulfate monohydrate, and 2-3 parts anhydrous sodium tetraborate.
[0009] By employing the above technical solution, this invention tends to construct a sustained-release framework with bulk diffusion characteristics, and, combined with the enzyme activity inhibition pathway of the local microenvironment, attempts to control the release rate of ammonia nitrogen from both physical and biochemical reaction dimensions. In the specific preparation and action system, anhydrous sodium tetraborate dissociates into borate ions during processing. These ions, acting as cross-linking agents, can typically undergo dehydration condensation reactions with the ortho-dihydroxyl and aliphatic alcohol hydroxyl groups on the sodium lignosulfonate framework, thereby generating borate ester bonds.
[0010] Based on this reaction, free lignin molecular chains intertwine to form a three-dimensional cross-linked network framework, with urea molecules dispersed and filling the interior of this macromolecular network. When the product is chewed by ruminants and new surfaces are exposed, the urea molecules within it are still somewhat restricted by the steric hindrance of the macromolecular network. Release into the external environment relies more on the slow swelling and decomplexing of the cross-linked network in the buffer solution, which helps mitigate the burst release problem caused by mechanical damage. Simultaneously with the construction of this network structure, zinc sulfate monohydrate releases zinc ions into the system. Due to their empty orbitals, these ions readily interact with the lone pair electrons of the oxygen atoms on the carbonyl groups of urea molecules.
[0011] This coordination effect reduces the force constant of the carbonyl double bond to some extent, strengthening the binding state between metal ions and nitrogen source components. When the compound feed enters the rumen buffer, the aforementioned coordination structure gradually dissociates along with the swelling of the three-dimensional network, and zinc ions and free urea tend to dissolve synchronously in the local microenvironment. The released trace amounts of zinc ions enter the fermentation broth and may competitively bind to the metal coordination sites of the active centers of free urease secreted by environmental microorganisms, thereby reducing the catalytic activity of urease. This, overall, helps to limit the rate of urea conversion to ammonia nitrogen.
[0012] Preferably, the compound feed is made from raw materials comprising the following parts by weight: 78 parts urea, 14 parts sodium lignosulfonate, 6 parts zinc sulfate monohydrate, and 2 parts anhydrous sodium tetraborate.
[0013] By adopting the above technical solution, it is helpful to achieve a relative balance between the crosslinking density and nitrogen source content in the system, reducing the risk of excessive product hardness due to a high proportion of crosslinking agent, which would affect palatability. At the same time, it provides steric hindrance conditions for maintaining a certain sustained-release period.
[0014] Preferably, the sodium lignosulfonate has a weight-average molecular weight (Mw) of 5000 Da to 10000 Da; the polymer structure of the sodium lignosulfonate contains guaiac-based and syringyl structural units with ortho-dihydroxyl and aliphatic alcohol hydroxyl functional groups.
[0015] By adopting the above technical solution, the moderate weight-average molecular weight is beneficial for the raw material to exhibit good rheological properties in the molten state, thus meeting processing requirements. The ortho-diphenolic hydroxyl and aliphatic alcoholic hydroxyl functional groups present in its skeleton can serve as active sites for cross-linking reactions, playing a positive role in promoting the formation and transformation of borate ester bonds.
[0016] Preferably, the urea contains ≥46.0wt% nitrogen and ≤0.5wt% moisture; the zinc sulfate monohydrate contains ≥35.0wt% zinc.
[0017] By adopting the above technical solutions, controlling the free moisture content in the raw materials helps to reduce the interference of moisture on the urea phase change process under high temperature conditions; at the same time, maintaining an appropriate amount of zinc is beneficial to maintaining the inhibitory effect on free urease activity.
[0018] Preferably, the mass fraction of biuret, a byproduct of urea pyrolysis, contained in the compound feed is not higher than 0.56%.
[0019] By adopting the above technical solutions, the content of biuret can be controlled at a low level, which helps to reduce its adverse effects on the digestive system of ruminants, thereby improving the safety of compound feed in feeding applications.
[0020] This invention provides a method for preparing a compound feed to increase milk production in lactating cows, using the following technical solution:
[0021] A method for preparing a compound feed to increase milk production in lactating cows includes the following steps:
[0022] S1. Heat the urea until it is completely melted into a homogeneous transparent melt, and start stirring;
[0023] S2. Add the anhydrous sodium tetraborate and the zinc sulfate monohydrate to the urea melt obtained in S1, increase the stirring speed and keep the temperature constant while stirring continuously.
[0024] S3. Subsequently, sodium lignosulfonate is added to the melt after the reaction in S2. The stirring is switched to high shear dispersion mode, and the constant temperature is maintained while the reaction is continuously stirred to trigger cross-linking and thickening.
[0025] S4. The melt after the reaction in S3 is completed is continuously output and subjected to contact cooling to solidify the material into a glassy state, thus obtaining a solid slow-release non-protein nitrogen compound feed.
[0026] By employing the above-mentioned technical solution, this preparation process attempts to combine chemical crosslinking with kinetic control. Under normal circumstances, the thermal deamination and condensation of two molecules of urea into biuret exhibits thermodynamic characteristics that are both temperature- and time-dependent.
[0027] In this operation, anhydrous sodium tetraborate and zinc sulfate monohydrate were pre-dispersed in the urea melt. When sodium lignosulfonate was subsequently added, the high-shear dispersion facilitated the extension of the macromolecular chains, thereby promoting the cross-linking condensation between borate ions and hydroxyl groups.
[0028] This chemical bonding often leads to a significant increase in the apparent viscosity of the material within a short period of time. It is this rheological thickening change that guides the material closer to its discharge state, objectively reducing the time window for the mixture to remain in the high-temperature melting phase. Through this time control in the process flow, the accumulation of activation energy and the probability of collisions in urea molecules are relatively limited, which is of practical significance for delaying or inhibiting the formation of biuret byproducts.
[0029] Preferably, in step S1, the urea is heated to a temperature of 133°C to 136°C; the stirring speed is set to 60 rpm to 80 rpm.
[0030] By adopting the above technical solution, urea is set within a slightly superheated critical temperature range. This temperature range can generally support urea to complete the solid-liquid phase transition to form the flow system required for the reaction, while also helping to mitigate the rapid decomposition caused by a high initial temperature.
[0031] Preferably, in step S2, the stirring speed is increased to 120 rpm to 150 rpm; the temperature of the constant temperature stirring reaction is controlled at 133°C to 136°C, and the reaction time is 4 min to 6 min.
[0032] By employing the above technical solution, a corresponding shear flow field is established within the system by increasing the rotational speed. This operation facilitates the dispersion of solid inorganic salts in high-viscosity melts, providing relatively uniform metal coordination ions and crosslinking agent sources for subsequent reactions, thereby reducing the problem of uneven gelation caused by local concentration differences.
[0033] Preferably, in step S3, the rotation speed of the high-shear dispersion mode is set to 250 rpm to 300 rpm; the temperature of the constant-temperature and continuously stirred reaction is controlled at 133°C to 136°C, and the reaction time is controlled at 3 min to 4 min.
[0034] By adopting the above technical solution, mechanical shearing helps overcome the fluid resistance generated by polymer addition and accelerates the dispersion process of the lignin skeleton. A constant temperature reaction period of 3 to 4 minutes is well-suited to the gelation time characteristics of in-situ borosilicate esterification reactions, facilitating the termination of mixing when the material reaches a suitable viscosity for unloading.
[0035] Preferably, step S4 is implemented as follows: the discharge valve of the reaction equipment is opened, and the melt in the reactor is continuously pumped into the feed trough of the rotary drum flaking machine. Cooling water with a constant temperature of 15℃~25℃ is introduced into the inside of the rotary drum. After the material comes into contact with the surface of the rotary drum, it undergoes glassy condensation and solidification, and then the final product is obtained by peeling it off with a scraper.
[0036] By employing the above technical solution, contact heat transfer is used to rapidly cool the high-temperature cross-linked melt. The condensation and solidification process helps maintain the initially formed internal network framework and slows down the subsequent reactions of residual components, which is beneficial for maintaining the stability of the physical morphology of the finished product and the relative integrity of its internal structure.
[0037] This invention provides a compound feed to increase milk production in lactating cows. It has the following beneficial effects:
[0038] 1. This invention utilizes the cross-linking of borate ions from anhydrous sodium tetraborate with the hydroxyl groups of sodium lignosulfonate to form a three-dimensional cross-linked network framework within the compound feed, dispersing urea molecules within this network structure. This structural feature transforms urea release into a slow swelling and decomplexing process dependent on the polymer network, overcoming the defect of traditional surface-coated feeds where the coating breaks down after mechanical chewing by ruminants, leading to burst release. When the product exposes a new cross-section, the internal cross-linked network still provides steric hindrance, maintaining the stability of the feed's slow-release performance in the rumen.
[0039] 2. This invention utilizes zinc sulfate monohydrate to provide zinc ions within the system, forming a coordination structure with urea molecules. Combined with the aforementioned physical cross-linking network, a two-dimensional control mechanism for ammonia nitrogen release is established. When the formulated feed enters the rumen buffer system, zinc ions dissolve simultaneously with free urea. The trace amounts of released zinc ions can competitively bind to the coordination sites of free urease active sites in the environment. This process reduces the catalytic activity of urease at the biochemical level, slowing down the rate of urea conversion to ammonia, which helps control the peak concentration of ammonia nitrogen in the rumen and reduces the risk of ammonia poisoning in animals.
[0040] 3. This invention combines chemical crosslinking with rheological changes in its preparation process. By adding sodium lignosulfonate to urea melt containing inorganic salts and coordinating with high-shear dispersion, a rapid borosilicate crosslinking reaction is triggered. This chemical bonding process leads to a rapid increase in the apparent viscosity of the material, prompting the processing to reach the discharge state more quickly and objectively shortening the residence time of the mixture in the high-temperature melting environment. This time limitation of the process inhibits the thermodynamic process of urea molecule deammoniation condensation, controlling the generation of pyrolysis byproducts such as biuret to a low range, thus ensuring the safety of non-protein nitrogen feed in practical applications. Attached Figure Description
[0041] Figure 1 The pure raw materials of this invention and the product of Example 2 were subjected to a temperature of 4000 cm. -1 Up to 400cm -1 Stacked comparison of Fourier transform infrared spectra across the entire spectrum;
[0042] Figure 2 The rheological dynamic test curves of Example 2 and Comparative Example 1 of the present invention are shown; wherein, (a) is a comparison trajectory of the apparent viscosity change of Example 2 and Comparative Example 1 during the test period, and (b) is the dynamic evolution trajectory of the storage modulus and loss modulus of Example 2 over time.
[0043] Figure 3 The following is a comparison of the in vitro nitrogen release dynamic characteristics of each group of samples after pulverization; wherein, (a) is the continuous urea cumulative release rate curve based on discrete sampling point interpolation fitting, and (b) is the instantaneous release rate dynamic change curve obtained by differentiating the cumulative release curve.
[0044] Figure 4 The diagram shows the continuous fermentation kinetics evolution of urease activity and ammonia nitrogen concentration in the in vitro simulated fermentation system of the present invention; wherein, (a) is the dynamic trend of urease activity in the fermentation broth system of Example 2 and Comparative Example 3, and (b) is the dynamic trend of ammonia nitrogen concentration in the fermentation broth system of Example 2 and Comparative Example 3.
[0045] Figure 5 This is a schematic diagram of the high-performance liquid chromatography separation of biuret components in the sample of this invention. Detailed Implementation
[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] This invention provides a compound feed to increase milk production in lactating cows. The main raw materials and reagents used in the following examples and comparative examples are as follows. Unless otherwise specified, all reagents are commercially available analytical grade or higher grade products.
[0048] Urea, CAS No. 57-13-6, industrial grade, nitrogen content ≥46.0wt%, biuret content ≤1.0wt%, moisture content ≤0.5wt%.
[0049] Sodium lignosulfonate, CAS No. 8061-51-6, industrial grade, with a weight-average molecular weight (Mw) of 5000 Da to 10000 Da, contains guaiac-based and syringyl structural units with ortho-diphenolic hydroxyl and aliphatic alcohol hydroxyl functional groups in its polymer structure.
[0050] Zinc sulfate monohydrate, CAS No. 7446-19-7, industrial grade, purity ≥98.0wt%, zinc content ≥35.0wt%.
[0051] Anhydrous sodium tetraborate, CAS No. 1330-43-4, industrial grade, purity ≥99.0wt%.
[0052] Example 1:
[0053] This embodiment provides a compound feed to increase milk production in lactating cows, including the following steps:
[0054] 75 kg of urea was added to a reactor equipped with a heat transfer oil heating jacket and a variable frequency speed stirrer. The heating was turned on to raise and maintain the temperature of the material in the reactor to 133°C. After the urea was completely melted into a homogeneous transparent melt, the stirrer was started and the speed was set to 60 rpm.
[0055] Add 2 kg of anhydrous sodium tetraborate and 8 kg of zinc sulfate monohydrate to the urea melt at 133°C, increase the stirrer speed to 120 rpm, and stir continuously at 133°C for 4 min.
[0056] Then, 15 kg of sodium lignosulfonate was added to the molten liquid in the reactor, and the stirrer was immediately switched to high shear dispersion mode, the speed was increased to 250 rpm, the temperature inside the reactor was maintained at 133℃, and the reaction was stirred for 4 minutes.
[0057] Open the discharge valve at the bottom of the reactor to continuously pump the melt inside the reactor into the feed trough of the rotary drum flaking machine. Cooling water at a constant temperature of 15°C is introduced into the inside of the rotary drum. After the material comes into contact with the surface of the rotary drum, it undergoes glass solidification. After being peeled off by a scraper, a solid slow-release non-protein nitrogen compound feed is obtained.
[0058] Example 2:
[0059] This embodiment provides a compound feed to increase milk production in lactating cows, including the following steps:
[0060] 78 kg of urea was added to a reactor equipped with a heat transfer oil heating jacket and a variable frequency speed stirrer. The heating was turned on to raise and maintain the temperature of the material in the reactor to 135°C. After the urea was completely melted into a homogeneous transparent melt, the stirrer was started and the speed was set to 70 rpm.
[0061] Add 2 kg of anhydrous sodium tetraborate and 6 kg of zinc sulfate monohydrate to the urea melt at 135°C, increase the speed of the stirrer to 135 rpm, and stir continuously at 135°C for 5 min.
[0062] Then, 14 kg of sodium lignosulfonate was added to the molten liquid in the reactor, and the stirrer was immediately switched to high shear dispersion mode, the speed was increased to 280 rpm, the temperature inside the reactor was maintained at 135℃, and the reaction was stirred for 3 minutes.
[0063] Open the discharge valve at the bottom of the reactor to continuously pump the melt inside the reactor into the feed trough of the rotary drum flaking machine. Cooling water at a constant temperature of 20°C is introduced into the inside of the rotary drum. After the material comes into contact with the surface of the rotary drum, it undergoes glass solidification. After being peeled off by a scraper, a solid slow-release non-protein nitrogen compound feed is obtained.
[0064] Example 3:
[0065] This embodiment provides a compound feed to increase milk production in lactating cows, including the following steps:
[0066] Add 80 kg of urea into a reactor equipped with a heat transfer oil heating jacket and a variable frequency speed stirrer. Turn on the heating to raise and maintain the temperature of the material in the reactor to 136°C. After the urea has completely melted into a homogeneous transparent melt, start the stirrer and set the speed to 80 rpm.
[0067] Add 3 kg of anhydrous sodium tetraborate and 7 kg of zinc sulfate monohydrate to the urea melt at 136°C, increase the stirring speed to 150 rpm, and stir continuously at 136°C for 6 min.
[0068] Then, 10 kg of sodium lignosulfonate was added to the molten liquid in the reactor, and the stirrer was immediately switched to high shear dispersion mode, the speed was increased to 300 rpm, the temperature inside the reactor was maintained at 136°C, and the reaction was continued for 4 minutes.
[0069] Open the discharge valve at the bottom of the reactor to continuously pump the melt inside the reactor into the feed trough of the rotary drum flaking machine. Cooling water at a constant temperature of 25°C is introduced into the inside of the rotary drum. After the material comes into contact with the surface of the rotary drum, it undergoes glass solidification. After being peeled off by a scraper, a solid slow-release non-protein nitrogen compound feed is obtained.
[0070] Comparative Example 1:
[0071] Compared with Example 2, the difference is that anhydrous sodium tetraborate was not added, and its mass fraction was replaced with an equal mass of urea. The other raw material types, amounts and preparation processes are the same.
[0072] Comparative Example 2:
[0073] Compared with Example 2, the difference is that sodium lignosulfonate was not added, and its mass fraction was replaced with an equal mass of urea; otherwise, they are the same.
[0074] Comparative Example 3:
[0075] Compared with Example 2, the difference is that zinc sulfate monohydrate was not added, and its mass fraction was replaced with an equal mass of urea; otherwise, they are the same.
[0076] Comparative Example 4:
[0077] Compared with Example 2, the difference lies in the preparation method. All raw materials are directly physically mixed and compressed into tablets at room temperature, without heating, melting, or high-shear crosslinking reactions. All other aspects are the same.
[0078] Test Example 1:
[0079] Pure urea, pure sodium lignosulfonate, and the finished product prepared in Example 2 were used as test samples. Each sample was placed in a vacuum drying oven and dried at 45°C for 24 hours to remove moisture.
[0080] Weigh approximately 1.5 mg of each dried sample and mix and grind them evenly with approximately 150 mg of dried potassium bromide powder in an agate mortar. Then transfer the mixed powder into a mold and press it under a pressure of 10 MPa for 2 minutes to obtain potassium bromide test tablets.
[0081] The compressed tablet was placed in a Fourier transform infrared spectrometer for transmission mode scanning. The scanning range was set to 4000 cm⁻¹. -1 Up to 400cm -1 The resolution is 4cm. -1 The number of scans was set to 32. Baseline subtraction was performed using a blank potassium bromide pellet as the background, and the infrared spectral data of each sample were exported and characteristic peak parameters were extracted.
[0082] Table 1. Positions of infrared absorption peaks of characteristic functional groups and relative transmittance test results for each sample.
[0083] Sample Name <![CDATA[Carbonyl stretching vibration peak position (cm -1 )]]> <![CDATA[Amino group stretching vibration peak position (cm -1 )]]> Transmittance of characteristic peak of o-dihydroxyl group (%) <![CDATA[B-O-C characteristic peak position (cm -1 )]]> Pure urea 1682.4 3442.8 - - Sodium lignosulfonate - - 31.7 Not detected Example 2 Product 1656.7 3435.1 74.2 1394.2
[0084] Based on the data in Table 1 and the appendix Figure 1In Example 2, the carbonyl stretching vibration peak of urea in the product decreased from 1682.4 cm⁻¹ in pure urea. -1 A clear redshift to lower wavenumbers was observed, reaching 1656.7 cm⁻¹. -1 This redshift phenomenon suggests that there may be coordination or strong interaction between Zn2+ and the oxygen atom of the carbonyl group in the urea molecule, thereby reducing the force constant of the carbonyl double bond. This provides spectroscopic evidence for the formation of an interaction structure between zinc ions and urea in the eutectic system, and provides a structural basis for the regulation of urease activity during the subsequent release process. Meanwhile, compared with pure sodium lignin sulfonate, the product of Example 2 showed a redshift at 1394.2 cm⁻¹. -1 A distinct BOC stretching vibration characteristic absorption peak appeared, and the transmittance of the absorption peak, which originally reflected the characteristics of the ortho-dihydroxyl group, increased from 31.7% to 74.2%, indicating a significant decrease in its absorption intensity. This suggests that the borate ions dissociated from anhydrous sodium tetraborate may react with the ortho-dihydroxyl or aliphatic alcohol hydroxyl groups on the lignin framework in shear melts above 133°C, forming borate ester bonds or borate ester-type cross-linked structures. The above detection results support the in-situ formation of a three-dimensional network framework within the critical temperature range where urea deammoniation condensation does not occur significantly, thereby limiting the rapid migration of urea molecules and zinc ions in the solid product, demonstrating the chemical feasibility of the thermodynamic reconstruction mechanism of this invention.
[0085] Test Example 2:
[0086] The test fixture of the rotary rheometer with heating system is set to a coaxial cylindrical rotor. The temperature control system is activated and the temperature of the test chamber is kept constant at 135℃.
[0087] According to the raw material types and mass ratios of Example 2 and Comparative Example 1, the corresponding mass of trace experimental samples were calculated and weighed to form parallel test groups.
[0088] Urea from both groups of materials was separately added to the rheometer test chamber. After heating and transforming into a homogeneous melt, zinc sulfate monohydrate and anhydrous sodium tetraborate were added in corresponding proportions, respectively. In Comparative Example 1, anhydrous sodium tetraborate was not added, and an equal mass of urea was used to replace this component. The test was conducted at a shear rate of 50 s⁻¹. -1 Under constant temperature mixing and pretreatment conditions, the mixture was subjected to a 4-minute pretreatment.
[0089] While maintaining constant temperature and shear rate, sodium lignosulfonate of each group was rapidly added to the test chamber in the corresponding proportions. Sodium lignosulfonate of each group was added in both Example 2 and Comparative Example 1, and the time scan test program of the rheometer was started simultaneously.
[0090] During the test, the apparent viscosity was at 50s. -1Rheological parameters were continuously recorded under constant shear rate conditions. Storage modulus and loss modulus were determined using a small-amplitude oscillation time-scan mode with an oscillation frequency of 1 Hz and the oscillation strain controlled within the linear viscoelastic region. Rheological parameters were continuously collected within 5 minutes after the addition of sodium lignosulfonate, and data points on the changes in apparent viscosity, storage modulus, and loss modulus over time were recorded.
[0091] Table 2. Rheological parameter test results of Example 2 and Comparative Example 1 during isothermal shearing process
[0092] Test time (min) Example 2 Apparent viscosity (Pa·s) Example 2: Energy Storage Modulus (Pa) Example 2 Loss Modulus (Pa) Comparative Example 1: Apparent viscosity (Pa·s) Comparative Example 1: Storage Modulus (Pa) Comparative Example 1: Loss Modulus (Pa) 0.6 2.51 1.18 4.67 1.74 0.42 2.15 1.3 3.82 4.05 11.23 1.68 0.38 2.06 2.2 15.63 32.84 48.71 1.83 0.47 2.38 3.1 148.91 382.65 291.43 1.79 0.45 2.24 4.2 875.46 2954.12 1462.58 1.91 0.51 2.41 4.9 1342.18 5128.93 1853.47 1.86 0.49 2.33
[0093] Based on the data in Table 2 and the appendix Figure 2 In Example 2, during the initial testing phase (0.6 to 1.3 min) after the addition of sodium lignosulfonate, the system primarily exhibited viscous fluid characteristics. The loss modulus, reflecting viscous behavior, was greater than the storage modulus, reflecting elastic behavior, and the apparent viscosity remained relatively low. When the shear reaction progressed to the 2.2 to 3.1 min range, the storage modulus increased logarithmically and surpassed the loss modulus near 3 min, forming a modulus crossover point. Simultaneously, the apparent viscosity underwent a step-change. This rheological characteristic indicates that the material gradually transformed from a melt-dispersed state dominated by viscous flow to a networked gel state dominated by elastic response within a short period.
[0094] In contrast, Comparative Example 1, lacking anhydrous sodium tetraborate, exhibited an apparent viscosity that remained consistently low throughout the 5-minute test period, with the loss modulus consistently exceeding the storage modulus. This indicates that no significant intermolecular network crosslinking reaction occurred within the melt. These rheological parameters validate the successful implementation of the mechanism designed in this study, which utilizes sodium tetraborate and lignin to construct a macromolecular network crosslinking framework. Furthermore, the rapid thickening and crosslinking time window aligns with the theoretical expectations of a short-term thermal history process.
[0095] Test Example 3:
[0096] The finished products prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 4 were collected and placed in a laboratory micro plant pulverizer for high-intensity mechanical grinding. The ground materials were then passed through a standard test sieve with a pore size of 2 mm, and the material that passed through the sieve was collected to simulate the fragmented state after being chewed and broken by ruminants.
[0097] Accurately weigh 5.00g of each of the above-mentioned groups of sieved fragment samples, and place them into dialysis bags, tying both ends tightly. Place each dialysis bag into a dissolution vessel containing 500mL of artificial rumen buffer (pH adjusted to 6.5, temperature set at 39℃), and turn on the magnetic stirrer at 100rpm.
[0098] At 1h, 2h, 4h, 6h and 8h of reaction, 5mL of the released solution was taken from each dissolution vessel, and 5mL of blank artificial rumen buffer at the same temperature was immediately added to the dissolution vessel to maintain a constant volume.
[0099] The collected release solution was filtered through a 0.45 μm microporous membrane, and the filtrate was collected. The absorbance at 420 nm was measured on a UV-Vis spectrophotometer using the p-dimethylaminobenzaldehyde spectrophotometric method. The urea nitrogen concentration in the filtrate was calculated using the urea standard curve, and normalized to 100% of the theoretical total urea in each sample. The calculation was also corrected for the volume change caused by the addition of blank artificial rumen buffer after sampling, and converted into the cumulative urea release rate at each time point.
[0100] Table 3. Results of dynamic changes in the cumulative urea release rate of each sample after pulverization and destruction in vitro.
[0101] Sampling time (h) Example 2: Cumulative urea release rate (%) Comparative Example 1: Cumulative urea release rate (%) Comparative Example 2: Cumulative Urea Release Rate (%) Comparative Example 4: Cumulative Urea Release Rate (%) 1 16.43 64.21 67.85 86.12 2 27.58 83.74 86.42 96.35 4 43.91 94.18 95.73 98.71 6 61.27 97.45 98.66 99.82 8 79.05 98.83 99.14 99.95
[0102] Based on the data in Table 3 and the appendix Figure 3 In Comparative Example 4, prepared using a room-temperature physical mixing process, the internal components did not undergo chemical bonding. After mechanical crushing, the internal urea was directly exposed to the buffer solution, resulting in a cumulative release rate as high as 86.12% in the first hour, thus losing its controlled-release capability. Comparative Example 1 lacked the cross-linking agent anhydrous sodium tetraborate, and Comparative Example 2 lacked the macromolecular backbone sodium lignin sulfonate. Although both underwent a high-temperature eutectic process, a three-dimensional cross-linked network could not be constructed within the melt. This led to severe burst release phenomena after grinding and destruction, with release rates reaching 83.74% and 86.42% respectively in the second hour, indicating the failure of the surface physical water barrier under mechanical force. In contrast, the sample in Example 2, after undergoing the same intensity of crushing and destruction, had a release rate controlled at 27.58% in the first two hours, and then showed a gradual increasing release trend in the following six hours, with a release rate of 79.05% in the eighth hour. The test data above indicate that the borate ester crosslinking network formed in this scheme does not only exist on the particle surface, but also forms a network structure inside the material that can restrict the rapid diffusion of urea. When the product is damaged or a new exposed section is created, the urea molecules at the section are still restricted by the spatial steric hindrance of the macromolecular network. The release of urea into the external environment is limited by the slow swelling and decomplexing process of the crosslinking network over time, verifying the feasibility and technical advantages of the present invention in resisting mechanical damage by using a bulk diffusion mechanism instead of a physical coating mechanism.
[0103] Test Example 4:
[0104] Rumen fluid was collected from healthy lactating dairy cows with permanent rumen fistulas before morning feeding. The fluid was filtered through four layers of defatted gauze. The filtrate was mixed with artificial buffer solution pre-saturated with carbon dioxide at a volume ratio of 1:2 to prepare an in vitro fermentation culture medium. The entire process was carried out under constant temperature and anaerobic conditions at 39°C.
[0105] Accurately weigh the samples from Example 2 and Comparative Example 3, which provide equal amounts of nitrogen source, and place them in glass tubes for in vitro fermentation. Add an equal amount of crushed corn starch to each tube as the carbon source substrate for fermentation.
[0106] Inject 50 mL of the prepared in vitro fermentation culture medium into each fermentation tube containing the sample. After continuously purging the air from the tube with carbon dioxide gas, quickly seal it with a rubber stopper equipped with a one-way exhaust valve.
[0107] The sealed fermentation tubes were placed in a constant temperature water bath shaker, with the temperature set at 39℃ and the shaking frequency at 120 rpm. The fermentation broth was collected at the corresponding time points of 1h, 2h, 4h, 6h, and 8h of the simulated fermentation.
[0108] The collected fermentation broth was divided into two portions. The first portion was centrifuged at 4000 rpm for 10 minutes in a refrigerated centrifuge, and the supernatant was collected. The absorbance at 630 nm was measured using a visible spectrophotometer with the phenol-sodium hypochlorite colorimetric method to calculate the ammonia nitrogen concentration in the system. The second portion of fermentation broth was treated with an ultrasonic cell disruptor, and the total urease activity in the system was determined using the indophenol blue colorimetric method with a urease assay kit.
[0109] Table 4. Results of dynamic changes in urease activity and ammonia nitrogen concentration in the in vitro fermentation systems of Example 2 and Comparative Example 3
[0110] Sampling time (h) Example 2 Total urease activity (U / L) Example 2: Ammonia nitrogen concentration (mg / dL) Comparative Example 3: Total urease activity (U / L) Comparative Example 3: Ammonia nitrogen concentration (mg / dL) 1 24.16 6.83 47.92 14.28 2 21.34 11.27 53.15 32.54 4 18.57 15.61 51.08 48.76 6 19.82 18.39 45.24 35.12 8 17.05 16.42 41.77 21.09
[0111] Based on the data in Table 4 and the appendix Figure 4 In Comparative Example 3, due to the lack of zinc sulfate monohydrate, the urease activity in the fermentation broth remained between 41.77 and 53.15 U / L throughout the fermentation cycle. This high enzyme activity led to the rapid hydrolysis of released urea, causing the ammonia nitrogen concentration in the system to surge to 48.76 mg / dL at the 4th hour, exceeding the risk threshold for animal tolerance. This indicates that physical controlled release relying solely on cross-linked networks still carries the potential risk of excessively rapid urea decomposition leading to localized ammonia accumulation in the face of complex microbial fermentation environments. In Example 2, zinc sulfate monohydrate was added, and its free urease activity was inhibited at a lower level of 17.05 to 24.16 U / L. The corresponding peak ammonia nitrogen concentration in the system was only 18.39 mg / dL, and the peak time was delayed until the 6th hour.
[0112] Test results indicate that zinc ions and urea molecules may form coordination or strong interaction structures in the eutectic system. As the macromolecular network swells, zinc ions and urea are released synchronously in the local microenvironment. The released zinc ions may interact with the metal coordination environment or key active sites of urease active centers, thereby reducing urease catalytic activity and limiting the rate of urea conversion to ammonia nitrogen. This local synchronous release and enzyme activity inhibition helps reduce the risk of rapid accumulation of free ammonia nitrogen and makes the nitrogen source release process more compatible with the carbon source fermentation and utilization process.
[0113] Test Example 5:
[0114] To prepare a control sample for Comparative Example 5, using the same raw material types and ratios as in Example 2, the set temperature of the reactor was increased to 145°C. After the urea was completely melted, anhydrous sodium tetraborate and zinc sulfate monohydrate were added, and the reaction was carried out at a constant temperature of 145°C for 10 minutes. Subsequently, sodium lignosulfonate was added, and the reaction was carried out at a constant temperature of 145°C for another 15 minutes, so that the total constant temperature reaction time after the addition of materials was 25 minutes. Finally, the material was discharged and the product was collected as a high-heat history control sample.
[0115] Accurately weigh 2.000g of each of the four groups of samples and place them in a 100mL volumetric flask. Add an appropriate amount of high performance liquid chromatography grade ultrapure water and place the flask in an ultrasonic water bath for 15 minutes to fully dissolve and desorb the sample particles. After cooling to room temperature, dilute to the mark with ultrapure water and shake well.
[0116] The extraction solutions in each volumetric flask were filtered using an aqueous microporous membrane with a pore size of 0.22 μm. The subsequent filtrate after discarding the initial filtrate was collected and placed into a chromatographic injection bottle with a Teflon septum as the sample solution to be tested.
[0117] The high-performance liquid chromatograph (HPLC) was turned on. A C18 reversed-phase column (250 mm × 4.6 mm, 5 μm) was used. The mobile phase was set to a mixture of ultrapure water and acetonitrile (90:10, v / v), the flow rate was controlled at 1.0 mL / min, the column temperature was kept constant at 30 °C, and the UV detector wavelength was set to 200 nm. 20 μL of each sample solution was injected into the chromatogram system, and the chromatograms were recorded. The mass percentage of biuret in each sample was calculated using a retention time and peak area external standard method curve established beforehand using biuret standards.
[0118] Table 5. HPLC determination results of biuret content in the finished products of the examples and comparative examples.
[0119] Sample Name Chromatographic peak retention time (min) Chromatographic peak area (mAU·s) Biuret mass fraction (%) Example 1 3.42 286.4 0.38 Example 2 3.41 342.7 0.45 Example 3 3.43 418.2 0.56 Comparative Example 5 3.41 1925.8 2.61
[0120] Based on the data in Table 5 and the appendix Figure 5In the final products of Examples 1 to 3, the mass fraction of biuret ranged from 0.38% to 0.56%. This data reflects that when the process was carried out within the critical slightly superheated melting temperature range of urea (133°C to 136°C), and the total isothermal reaction time was controlled to approximately 8 to 10 minutes with high shear, the urea molecules inside the melt did not accumulate sufficient activation energy and collision probability to initiate the deammoniation condensation mechanism in large quantities. In contrast, in Comparative Example 5, after increasing the reaction temperature to 145°C and extending the heating time to 25 minutes, the side reaction of two urea molecules condensing into biuret intensified rapidly, causing the mass fraction of biuret in the product to climb to 2.61%, significantly higher than the biuret content levels in Examples 1 to 3. This indicates that excessively high reaction temperatures and excessively long heating times increase the risk of biuret accumulation, which is detrimental to the safety control of ruminant animal consumption. The reaction of urea pyrolysis at high temperature to generate biuret and its derivative polymers follows a time- and temperature-dependent thermodynamic path. In this scheme, the design of a trace amount of sodium tetraborate crosslinking agent triggering a second-level gelation reaction in the lignin skeleton can force material thickening, discharge, and cooling at the instant the spatial network reconstruction is completed. This rapid solidification at the mechanistic level interrupts the reaction time window for biuret formation, confirming that this process is feasible and necessary for controlling the safety risks of ingestion by ruminants while simultaneously achieving in-situ preparation of sustained-release structures.
[0121] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A compound feed for increasing milk production in lactating cows, characterized in that: The compound feed is made from the following raw materials in parts by weight: 75-80 parts urea, 10-15 parts sodium lignosulfonate, 6-8 parts zinc sulfate monohydrate, and 2-3 parts anhydrous sodium tetraborate.
2. The compound feed for increasing milk production in lactating cows according to claim 1, characterized in that, The compound feed is made from the following raw materials in parts by weight: 78 parts urea, 14 parts sodium lignosulfonate, 6 parts zinc sulfate monohydrate, and 2 parts anhydrous sodium tetraborate.
3. The compound feed for increasing milk production in lactating cows according to claim 1, characterized in that, The sodium lignosulfonate has a weight-average molecular weight (Mw) of 5000 Da to 10000 Da; the polymer structure of the sodium lignosulfonate contains guaiac- and syringyl structural units with ortho-dihydroxyl and aliphatic alcohol hydroxyl functional groups.
4. The compound feed for increasing milk production in lactating cows according to claim 1, characterized in that, The urea contains ≥46.0wt% nitrogen and ≤0.5wt% moisture; the zinc sulfate monohydrate contains ≥35.0wt% zinc.
5. The compound feed for increasing milk production in lactating cows according to claim 1, characterized in that, The compound feed has a three-dimensional network cross-linked framework, which contains a borate ester cross-linked structure formed by the combination of borate ions dissociated from anhydrous sodium tetraborate and the hydroxyl groups of sodium lignosulfonate, and a coordination structure formed by the coordination of zinc ions in zinc sulfate monohydrate with the carbonyl oxygen atoms in urea molecules; and the mass fraction of biuret, a byproduct of urea pyrolysis, contained in the compound feed is not higher than 0.56%.
6. A method for preparing compound feed to increase milk production in lactating cows, characterized in that, Includes the following steps: S1. Heat the urea until it is completely melted into a homogeneous transparent melt, and start stirring; S2. Add anhydrous sodium tetraborate and zinc sulfate monohydrate to the urea melt obtained in S1, increase the stirring speed and keep the temperature constant while stirring continuously. S3. Then add sodium lignosulfonate to the melt after the reaction in S2, switch the stirring to high shear dispersion mode, maintain constant temperature and continue stirring to trigger cross-linking and thickening. S4. The melt after the reaction in S3 is completed is continuously output and subjected to contact cooling to solidify the material into a glassy state, thus obtaining a solid slow-release non-protein nitrogen compound feed.
7. The method for preparing a compound feed to increase milk production in lactating cows according to claim 6, characterized in that, In step S1, the urea is heated and maintained at 133℃~136℃; the stirring speed is set to 60rpm~80rpm.
8. The method for preparing a compound feed to increase milk production in lactating cows according to claim 6, characterized in that, In step S2, the stirring speed is increased to 120 rpm to 150 rpm; the temperature of the constant temperature continuous stirring reaction is controlled at 133℃ to 136℃, and the reaction time is 4 min to 6 min.
9. A method for preparing compound feed to increase milk production in lactating cows according to claim 6, characterized in that, In step S3, the rotation speed of the high-shear dispersion mode is set to 250 rpm to 300 rpm; the temperature of the constant-temperature and continuously stirred reaction is controlled at 133℃ to 136℃, and the reaction time is controlled at 3 min to 4 min.
10. A method for preparing compound feed to increase milk production in lactating cows according to claim 6, characterized in that, The specific implementation method of step S4 is as follows: open the discharge valve of the reaction equipment, continuously pump the melt in the reactor to the feed trough of the rotary drum flaking machine, and introduce cooling water with a constant temperature of 15℃~25℃ into the inside of the rotary drum. After the material comes into contact with the surface of the rotary drum, it undergoes glassy condensation and solidification, and then is peeled off by a scraper to obtain the final product.